The Importance of Roots - Pierson, Eric (Watching While Black, 2012)
In January 1977, I, along with over ninety million other Americans, watched at least one episode of the television miniseries Roots: The Saga of an American Family. Over the eight days of the broadcast, the audience grew, and debates regarding its impact filled media outlets. In the weeks and months after the show aired, the impact was measurable as many families sought out genealogists to research family histories and college campuses saw increased interest in African American Studies. Vernon Jordan, executive director of the National Urban League, commented, “ Roots was the single most spectacular educational experience in race relations in
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)